2014
DOI: 10.1371/journal.pone.0105517
|View full text |Cite
|
Sign up to set email alerts
|

Breast Contrast-Enhanced Ultrasound: Is a Scoring System Feasible? ----A Preliminary Study in China

Abstract: ObjectivesAlthough many studies about breast contrast-enhanced ultrasound had been conducted, clear diagnostic criteria for evaluating enhancement patterns are still lacking. This study aims to identify significant indicators for breast contrast-enhanced ultrasound and to establish an initial scoring system.Materials and MethodsTotally 839 patients were included in the study. This study was divided into two parts. 364 patients were included in part 1 while 475 in part 2. Conventional ultrasound and contrast-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 48 publications
2
34
1
Order By: Relevance
“…However, vessel path and distribution inside the lesions were more clearly observed on mSMI than on MVI (Figure 1). Secondly, peripheral radial vessels, a good indicator for malignant lesions, 14,16,21 were more commonly seen on MVI than on mSMI ( Figure 2). The reason might be the difficulty in distinguishing blood flows from noises generated when subtracting the high-echo tissues outside the lesions by mSMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vessel path and distribution inside the lesions were more clearly observed on mSMI than on MVI (Figure 1). Secondly, peripheral radial vessels, a good indicator for malignant lesions, 14,16,21 were more commonly seen on MVI than on mSMI ( Figure 2). The reason might be the difficulty in distinguishing blood flows from noises generated when subtracting the high-echo tissues outside the lesions by mSMI.…”
Section: Discussionmentioning
confidence: 99%
“…cannula within 1-2 s, followed by injection of 5-10 ml of saline water. 21 Real-time images were recorded for up to 120-180 s for further analysis. MVI mode was initiated when the amount of microbubbles was adequate, and the cumulative images were captured.…”
Section: Ultrasonographic Examinationmentioning
confidence: 99%
“…Heterogeneity may have arisen from the inclusion criteria, US devices and probe frequencies. The variations among studies in the stage of included lesions may introduce differences in malignant frequency in study populations, affecting the diagnostic performance of an ultrasound technique (Du et al 2012;Liu et al 2008;Xiao et al 2014Xiao et al , 2016Zhang et al 2014). In the studies comprising this meta-analysis, a total of 8 ultrasound systems were used: (Esatune (Ricci et al 2007), Esaote (Zhao et al 2010), HDI 5000 (Liu et al 2008), Philips IU22 (An et al 2014;Liu et al 2008;Xiao et al 2014), AplioXG Miyamoto et al 2014], Prosound α10 (Miyamoto et al 2014), LOGIQ E9 and LOGIQ 9 (Zhang et al 2014)), with the probe frequencies ranging 5 MHz-15 MHz, either of which might cause the heterogeneity among studies.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Potential heterogeneity sources may include variations in contrast techniques, software for CEUS imaging processing or criteria for diagnosing malignancy. Here too, various manufacturers use various contrast techniques, such as Contrast-Tuned Imaging of Esaote (Du et al 2012;Le et al 2012;Ricci et al 2007;Zhao et al 2010), Coded Harmonic Angio of GE (Miyamoto et al 2014;Zhang et al 2014) and Pulse Inversion Harmonic Imaging of Philips (An et al 2014;Liu et al 2008;Xiao et al 2014Xiao et al , 2016, etc. Furthermore, various quantitative analysis software was used in some studies, such as Q-lab (An et al 2014;Liu et al 2008) and Qontrast (Du et al 2012;Le et al 2012;Ricci et al 2007;Zhao et al 2010).…”
Section: Heterogeneitymentioning
confidence: 99%
“…Only about 15% to 40% of screening mammograms with abnormal results and 25% to 50% of palpable lumps recommended for biopsy will result in malignant diagnoses . Although mammography and conventional grayscale ultrasound (US) remain the standard imaging modalities for breast lesions, prior studies have shown that contrast‐enhanced ultrasound (CEUS) may help distinguish benign and malignant breast masses . Microbubble contrast agents used in CEUS stay within the blood pool and show enhancement if the mass is solid and has vascular flow, indicating angiogenesis, a known characteristic of malignant breast lesions …”
mentioning
confidence: 99%